FEMALE AGENCY AND SPATIAL POLITICS IN CONTEMPORARY DYSTOPIAN FICTION (Contemporary Journal of Social Science Review, 2025)
This qualitative study is based on the examination of the portrayal of female agency and resistance against the spatial politics in the contemporary dystopian fiction, with respect to Atwood’s renowned work, The Year of the Flood (2009).  Viewing the literal and metaphorical representation of confinement, the paper analyzes the way that the female literary persona is shown navigating and challenging restrictive environments in the novel. The study draws upon spatial studies and feminist theory, arguing that the novel depicts female as subjugated by patriarchal control and detention in particular spaces such as God’s Gardener’s Compound the MaddAddamite environment, the post-apocalyptic landscape. Simultaneously, the paper examines how females devise strategies of subversion and resistance, and eventually mange to escape both ideologically and physically. The study indicates how these very cramped spaces then serve as the sites for liberation, exposure and empowerment, nurturing solidarity, alternative forms of knowledge and rebellion. By examining the interrelation between spatial confinement, female agency and the prospects of revitalization of society, the novel throws light on the ways that modern day dystopian fiction addresses issues related to gender, power and the viability of resistance within the apparently inescapable systems of control.